Benefits and Limitations of Waste-to-Energy Conversion in Iran - Ahmadi, A.; Esmaeilion, F.; Esmaeilion, A.; Ehyaei, M. A.; Silveira, J. L. [UNESP] (Shahrood Univ Technology, 2020)
In the developing countries such as Iran, a massive amount of municipal solid wastes is collected in the form of landfills. These wastes are major sources of soil and water pollutions. Due to the increase in the population of cities and the demand for energy, conversion of waste into energy is one of the most effective tools in waste management and energy generation. In this paper, the process of conversion of waste-to-energy (WTE) in Iran is investigated, and the future situation is estimated. Also the trends of waste management methods and energy production are evaluated. At the end, the benefits of the WTE process in the capital of Iran, i.e. Tehran, are observed. The WTE facilities in waste management are used within 3 regions of 22 metropolitan areas of Tehran serving 950,000 citizens. With manufacturing new WTE plants in Iran, it would be possible to prevent the burning of about 15 million barrels of oil or 255?107 cubic meters of natural gas annually, and use these fossil fuels to produce petrochemicals and export them. The associated overall expenses of WTE are also estimated in different countries at a rate of GDP between 300 and 3,000 $ per ton of MSW. Substituting WTE plants instead of oil basic plants can reduce about 0.13 kg/kWh CO2 emission, while most of the power plants are gas basic, which will have an increase of CO2 emissions of about 0.19 kg/kWh, although the cost of producing 1 MWh of electricity by WTE is estimated at around 110 USD. However, the payback period could be between 17 to 20 years.
Keywords: Waste-to-Energy; Municipal Solid Waste; Incineration; Sustainability; Renewable Energy; Iran